2005
DOI: 10.1038/sj.hdy.6800672
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Bayesian estimates of genetic differentiation of molecular markers and quantitative traits: an application to Pinus sylvestris

Abstract: Comparison of the level of differentiation at neutral molecular markers (estimated as F ST or G ST ) with the level of differentiation at quantitative traits (estimated as Q ST ) has become a standard tool for inferring that there is differential selection between populations. We estimated Q ST of timing of bud set from a latitudinal cline of Pinus sylvestris with a Bayesian hierarchical variance component method utilizing the information on the pre-estimated population structure from neutral molecular markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
1
28
1
4
Order By: Relevance
“…The transferability of SSR between Scots pine and P. taeda was previously demonstrated successfully (e.g., RobledoArnuncio et al 2005;Waldmann et al 2005;García-Gil et al 2009;Robledo-Arnuncio et al 2009). However, the transferability of our two multiplexes to other Pinus species required the initial testing of the expected sizes of the involved loci to avoid overlapping.…”
Section: Ssr Multiplex Transferabilitymentioning
confidence: 85%
See 1 more Smart Citation
“…The transferability of SSR between Scots pine and P. taeda was previously demonstrated successfully (e.g., RobledoArnuncio et al 2005;Waldmann et al 2005;García-Gil et al 2009;Robledo-Arnuncio et al 2009). However, the transferability of our two multiplexes to other Pinus species required the initial testing of the expected sizes of the involved loci to avoid overlapping.…”
Section: Ssr Multiplex Transferabilitymentioning
confidence: 85%
“…In conifers, nSSRs are applied in multiple research areas such as population studies (e.g., Marshall et al 2002;A 0 Hara and Cottrell 2004;Waldmann et al 2005;García-Gil et al 2009;Gugerli et al 2009;Tollefsrud et al 2009), genetic map construction (Pelgas et al 2006;Echt et al 2011) and paternity analysis (Lian et al 2001;Torimaru et al 2009). Despite the wide application of nSSRs, examples on the application of SSR multiplexing in conifers remain scarce (Devey et al 2002;Bell et al 2004;Karhu et al 2006;Gugerli et al 2009;Salzer et al 2009;Kawase et al 2010;Wagner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, if the parametric assumptions are reasonable, then this is not a problem. However, the assumptions underlying the parametric methods do need to be checked (Waldmann et al 2005), as was done here. If the assumptions are not correct then remedial action may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…This is apparently at odds with the observations of low levels of heterozygosity and limited genetic divergence identified in this study. It must be noted, however, that this study focused on neutral genetic markers, and there is growing evidence that neutral markers are poor indicators of adaptive or quantitative variation in conifers [30,70]. Within the Araucariaceae, a study of Araucaria araucana [5] found that neutral DNA markers (RAPDs) and quantitative variation were essentially uncorrelated.…”
Section: Limited Genetic Divergence Between Distant Provenancesmentioning
confidence: 94%